How to Enhance Mathematical Connection Ability of Junior High School Students in Indonesia - Ayu Agustianingsih; Shelly Morin; Veni Saputri (Didaktika: Jurnal Kependidikan, 2024)
Quality education is part of the Sustainable Development Goals (SDGs) and is important for developing critical thinking and problem solving skills in students. Mathematics as a basic discipline, plays an important role at all levels of education, including junior high school. Students' mathematical connection ability in linking mathematical concepts with various other fields and daily life, needs to be developed. However, research shows that students' mathematical connection ability are still low. This study aims to analyze and synthesize empirical findings related to students' mathematical connection ability to provide a deeper understanding. The method used in this research is systematic literature review (SLR) with three stages (planning, conducting, reporting). Data collection was obtained from data based Google Schoolar using the Publish or Perish application. The results showed that innovative learning models, such as RME, CORE, and PBL with multimedia, proved effective in enhancing students' mathematical connection ability.